Sexual Dimorphism in Motor Properties of Humans - Osiński, Wiesław; Swornowski , Piotr (Anthropological Review, 1983)
The aim of this paper is to analyze sexual dimorphism in following motor properties: isometric strength, standing high jump, standing triple jump, starting velocity and welocity in 100 meters dash, reaction times in response to acoustic and optic stimuli. Body height and mass were also considered, The material comprised 158 young females and 211 young males, candidates for studies at the Academy of Physical Education at Poznań. Statistical methods employed were: relative deviation of Mollison, Student's t test, Fisher's z test for comparisons between correlation coefficients and a method of variable grouping on grounds of similarity of correlation coefficients values. It has been found that males are much stronger and swifter than females, they are also better in jumping, females scored better only with respect to flexibility. The smallest sexual difference was found in time of response to the acoustic stimulus.